Transforming growth factor β1 enhances stemness of head and neck squamous cell carcinoma cells through activation of Wnt signaling - Bae, Woo-Jin (Oncol Lett, 2016)
Transforming growth factor β (TGFβ) ligands, including TGFβ1, are multifunctional cytokines known as key regulators of cell growth, differentiation and inflammation. Dysregulated TGFβ signaling is common in numerous solid tumors, including head and neck squamous cell carcinoma (HNSCC). Previously, TGFβ ligands were also reported to be associated with an enhancement of stemness in glioma stem-like cells. However, their role in HNSCC cancer stem cells (CSCs) has not been explored. The present study demonstrated that TGFβ1 enriches the properties of HNSCC CSCs. TGFβ1 promoted sphere formation and increased stemness-associated gene expression (Oct4 and Sox2) of primary HNSCC CSCs. Additionally, the population of aldehyde dehydrogenase (ALDH)-positive cells was increased subsequent to exogenous treatment of cells with TGFβ1. In addition, following stimulation with TGFβ1, the cells exhibited more resistance to cisplatin and elevated expression of Twist, Snail and Slug. Mechanistically, TGFβ1 acts as an upstream stimulator of Wnt/β-catenin signaling. Collectively, the present findings provide insights toward the development of TGFβ1 signaling inhibition strategies for treating HNSCC CSCs.